Case Study: An international study on CSR in five countries (Portugal, Bulgaria, Brazil, India and Greece): Effects on economic development, environmental sustainability and social welfare - Nagopoulos, N.; Rontos, K.; Yordanova, D. I.; Coelho, M.; Filipe, J.; Ferreira, M. A. M.; Mutharasu, S. A.; Figueredo, I. C. (Towards a society with a more fair economy or an economy with a more social face: The contribution of scientific social knowledge to the alternative models of socioeconomic development, 2015)
Corporate social responsibility (CSR) refers to companies'policies and actions aimed at achieving a positive impact on environment, consumers, employees or communities. It requires a set of duties self-regulating mechanisms and obligations, in relation to the society and to the communities in which the organization is operating. Corporate Social Responsibility is nowadays important enough to make that organizations put very challenging objectives in this area. In this Framework Companies shall ensure that law is guaranted as far as ethical standards and international norms shall be assured as well. There are many studies in the area of Corporate Social Responsibility but the presentation of several cases in one study reveals some particular aspects to be considered and to be had in account when CSR is studied. This study discusses the implications of CSR for economic development, environmental sustainability and social welfare in five countries.